ANALISIS PENGARUH E-WOM, CITRA WISATA, LOKASI, TERHADAP NIATAN BERKUNJUNG KE WISATA NEPAL VAN JAVA (Studi Kasus di Dusun Butuh, Kaliangkrik, Magelang) - Bustanul Alwi Farhani; Dimas Wibisono (DAS Institute, 2023)
This study aimed to identify and analyze E-Wom, Tourism Image, Location, Against Intentions to Visit Nepal Van Java Tourism in Need Hamlet. This type of research is survey research with a quantitative approach. The research design uses associative, namely, to determine the independent variable on the dependent variable. The primary data method and the data used in this study are primary data in the form of questionnaires given to respondents. The sample for this study was tourists who had visited the Nepal Van Java tour consisting of 160 respondents. The results of this study indicate that electronic word of mouth has a positive and significant effect on the intention to visit with a t-table value of 2.387, tourism image has a positive and significant effect on the intention to visit with a value of 2.914, location has a positive and insignificant effect on the intention to visit with a value of 0.346, and electronic word of mouth, tourist image, location has a positive and significant effect on the intention to visit with f count 5.939.